2013
DOI: 10.3329/jssmc.v5i1.16206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neem (Azadirachta Indica) on Fertility in Male Rats

Abstract: Background: Azadirachta indica locally known as neem has been claimed to possess antifertility properties by many investigators. Objective: The present study was designed to evaluate the antifertility effect of Azadirachta indica leaf powder in male rats. Methodology: The study was carried out in pharmacology and Therapeutic Department of Dhaka Medical College during the period of January 2008 to December 2008. Total number of 24 rats was divided into 4 groups. Group A was served as control, group B, C and D w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…There was a significant reduction in sperm cell concentration between the groups treated with A. indica (PAI LD and PAI HD ). This report correlates with observations of Khan et al [51] and Ofoego et al [52]. These workers reported reduction in sperm cell concentration, in contrast to Irais et al [53] who reported no reduction in sperm cell concentration following treatment with A. indica.…”
Section: Median Lethal Dose Of Azadirachta Indica and Gongronema Lati...supporting
confidence: 91%
“…There was a significant reduction in sperm cell concentration between the groups treated with A. indica (PAI LD and PAI HD ). This report correlates with observations of Khan et al [51] and Ofoego et al [52]. These workers reported reduction in sperm cell concentration, in contrast to Irais et al [53] who reported no reduction in sperm cell concentration following treatment with A. indica.…”
Section: Median Lethal Dose Of Azadirachta Indica and Gongronema Lati...supporting
confidence: 91%
“…Spermicidal activity is discovered in neem (Azadirachta indica). Sperm can be destroyed by neem leaf extract at a concentration of 200 mg/ml (Khan et al, 2013;Sharma and Maldonado, 2020).…”
Section: Spermicidementioning
confidence: 99%